Respuesta :
Answer:
y=3.5
Step-by-step explanation:
6x + 2y = 11
6(3) + 2y = 11
18 + 2y = 11
-18 -18
2y = - 7
/2 /2
y = -3.5
Answer:
y-intercept = 3.5
Step-by-step explanation:
The equation is given by the following straight line formula:
6x + 2y = 11
The y -intercept occurs when x = 0, that is, when x = 0, y is given by:
[tex]2y = 11\\ y = 5.5[/tex]
The x-intercept occurs when y = 0, then:
[tex]6x = 11\\ x = \frac{11}{6}[/tex]
Thus, the x-intercept is given by the point ([tex]\frac{11}{6}[/tex] , 0)
The x-intercept is given by the point (0 , 5.5)